2017
DOI: 10.1111/jvim.14633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delayed Digital Hypothermia on Lamellar Inflammatory Signaling in the Oligofructose Laminitis Model

Abstract: BackgroundIn the oligofructose (OF) model of sepsis‐related laminitis (SRL), digital hypothermia (“cryotherapy”) initiated before the onset of clinical signs is reported not only to limit lamellar injury, but also to cause marked inhibition of lamellar inflammatory signaling.Hypothesis/ObjectivesBecause hypothermia also has been reported to be protective when not initiated until the onset of lameness in the OF model of SRL, we hypothesized that the lamellar protection conferred by hypothermia is caused by loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Due to the findings of a previous study which demonstrated profound inhibition of a wide array of inflammatory mediators when CDH was instituted prior to either systemic sepsis or lamellar disease, CDH has been purported to limit lamellar injury due to its anti‐inflammatory effects. However, a more recent study in which CDH was initiated at the onset of clinical lameness (OG2) did not find the same degree of inhibition of lamellar inflammation with CDH despite it still conferring a dramatic protective effect upon the lamellae . Similarly, a recent study investigating the effects of CDH (instituted immediately after administration of enteral OF) on leukocyte infiltration in the OF SRL model reported only minor changes in lamellar leukocyte numbers, indicating that leukocyte infiltration may have less of a role in lamellar tissue damage than previously thought …”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Due to the findings of a previous study which demonstrated profound inhibition of a wide array of inflammatory mediators when CDH was instituted prior to either systemic sepsis or lamellar disease, CDH has been purported to limit lamellar injury due to its anti‐inflammatory effects. However, a more recent study in which CDH was initiated at the onset of clinical lameness (OG2) did not find the same degree of inhibition of lamellar inflammation with CDH despite it still conferring a dramatic protective effect upon the lamellae . Similarly, a recent study investigating the effects of CDH (instituted immediately after administration of enteral OF) on leukocyte infiltration in the OF SRL model reported only minor changes in lamellar leukocyte numbers, indicating that leukocyte infiltration may have less of a role in lamellar tissue damage than previously thought …”
mentioning
confidence: 90%
“…In contrast to previous studies of CDH, a non‐septic control group was incorporated into the study in order to (1) assess the effect of CDH on lamellar signaling in the normal limb, and (2) to be able to accurately assess whether CDH effectively inhibits inflammatory signaling in SRL to a level comparable to that observed in the normal limb. Additionally, in contrast to the study in which minimal anti‐inflammatory effect was detected when CDH was initiated at the onset of OG2 laminitis (where lamellar samples were harvested late in the disease process), the objective of the current study was to harvest samples at an earlier time point (prior to the onset of severe lamellar separation/failure) to avoid the effect that extensive structural tissue injury may have on inflammatory signaling.…”
mentioning
confidence: 99%
“…The IL-17 pathway upregulation observed here in natural cases of SLL is also likely present in laminitis associated with other risk factors. In models of SRL, one or more target genes of the IL-17 pathway have been identified as genes upregulated after experimental induction of laminitis [5; 15; 38; 39; 42-46; 52; 70]. One study in an SRL experimental model also hints that the IL-17 pathway may contribute to disease onset or progression.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of these studies used treatments that mimic SRL, although several reports also examined models of EL or SLL [15; 38-49]. Models of SRL provide the most evidence for inflammation, either through upregulation of inflammatory mediators [15; 38; 39; 42-47] or leukocyte infiltration [50-52]. Recently, a model to mimic some aspects of SLL was reported [48].…”
Section: Introductionmentioning
confidence: 99%
“…Horses that have clinical signs of endotoxaemia are at high risk of developing sepsisassociated laminitis. The oligofructose overload (OF) model has been used to study the pathogenesis of sepsis-associated laminitis [2][3][4][5][6][7][8]. These studies have also shown that continuous digital cryotherapy prevents the development and reduces the severity of sepsis-associated laminitis [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%